2010
DOI: 10.1186/1476-4598-9-39
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an alternative human CD133 promoter reveals the implication of Ras/ERK pathway in tumor stem-like hallmarks

Abstract: BackgroundAn increasing number of studies support the presence of stem-like cells in human malignancies. These cells are primarily responsible for tumor initiation and thus considered as a potential target to eradicate tumors. CD133 has been identified as an important cell surface marker to enrich the stem-like population in various human tumors. To reveal the molecular machinery underlying the stem-like features in tumor cells, we analyzed a promoter of CD133 gene using human colon carcinoma Caco-2 and synovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 57 publications
8
51
1
Order By: Relevance
“…Mutation analysis indicated that high CD133 expression was related to mutations in K-Ras or B-Raf. Interestingly, it was previously shown that activation of the Ras-Raf-MEK-ERK pathway can induce the activation of CD133 promoter 5 via its nuclear target Ets, thereby inducing CD133 expression (47). We confirmed this Ras dependency of CD133 mRNA and protein expression either by disrupting the mutant K-Ras allele in CRC cell lines or by inhibiting Ras downstream signaling.…”
Section: Discussionsupporting
confidence: 74%
“…Mutation analysis indicated that high CD133 expression was related to mutations in K-Ras or B-Raf. Interestingly, it was previously shown that activation of the Ras-Raf-MEK-ERK pathway can induce the activation of CD133 promoter 5 via its nuclear target Ets, thereby inducing CD133 expression (47). We confirmed this Ras dependency of CD133 mRNA and protein expression either by disrupting the mutant K-Ras allele in CRC cell lines or by inhibiting Ras downstream signaling.…”
Section: Discussionsupporting
confidence: 74%
“…Our results showed that short-term treatment with BMP4 could induce Erk1/2 activation in a time-and dose-dependent manner. In addition, the inhibition of Erk1/2 phosphorylation by a MEK1/ 2 inhibitor may lead to CD133 protein overexpression in HCC cell lines, which is distinct from the observation of CSCs in colon carcinoma (39). The MEK inhibitor nearly abolished the CD133 expression reduction resulting from the BMP4 treatment, and a short-term exposure to a high level of Erk1/2 phosphorylation plays an important role in BMP4 prodifferentiation effects.…”
Section: Discussionmentioning
confidence: 99%
“…moreover, the translational efficiency and stability of CD133 transcripts varied between 5' UTR sequences containing exon 1 (1A, 1B, 1C, 1D, or 1E). The 5' UTR region in CD133 is involved in the regulation of well-known proteins that regulate growth and differentiation of normal stem cells, and in the progression of specific types of cancers, such as leukemia and prostate cancer (23,36,37). Therefore, the role of exon1 in CD133 expression needs to be determined.…”
Section: Discussionmentioning
confidence: 99%